Knowledge of and attitudes toward clinical trials in Saudi Arabia: a cross-sectional study - Nedal Al-Rawashdeh; Rana Damsees; Majed Al-Jeraisy; Eman Al Qasim; Ahmad M Deeb (BMJ Open)
Objectives Clinical trials (CTs) are considered an important method for developing new treatments and providing access to potentially effective drugs that are still under investigation. Measuring the public’s knowledge of and attitudes toward CTs is important for assessing their readiness for and acceptance of human drug testing, which has previously not been assessed in the Kingdom of Saudi Arabia (KSA). The objective of this study is to explore the Saudi public’s knowledge of and attitudes toward CTs as well as participation in trials to test new or approved drugs.Design Cross-sectional.Setting The 2016 Al Jenadriyah cultural/heritage festival in Riyadh, KSA.Participants Participating booths and exhibition halls, as well as festival visitors, were approached to participate in the study.Primary and secondary outcome measures Knowledge of and attitudes toward CTs.Results The final number of participants was 938. The responses were converted to a percentage mean score (out of 100) for each knowledge-related response and attitude. The total mean knowledge score was 56.8±24.8 and the attitude-related score was 61.5±28.0. Although most of the participants supported testing approved or off-label and new drugs on adult and paediatric patients, only a third (30.5%) agreed that new drugs could be tested on healthy volunteers. The results indicated that gender, educational level, income, medical background, age and health insurance were independently associated with the level of knowledge of CTs. In terms of attitudes toward CTs, the factors that were independently associated were gender, educational level and medical background.Conclusions The Saudi public has a low level of knowledge and a moderately positive attitude toward CTs. There is a moderate positive correlation between the two factors such that as knowledge of CTs increases, the Saudi public will hold more positive attitudes toward CTs.